2011
DOI: 10.5194/cp-7-1011-2011
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variability at Dürres Maar, Germany during the Migration Period and at High Medieval Times, inferred from stable carbon isotopes of <i>Sphagnum</i> cellulose

Abstract: Abstract. This paper presents a high resolution reconstruction of local growing season temperature (GST) anomalies at Dürres Maar, Germany, spanning the last two millennia. The GST anomalies were derived from a stable carbon isotope time series of cellulose chemically extracted from Sphagnum leaves (δ 13 C cellulose ) separated from a kettle-hole peat deposit of several metres thickness. The temperature reconstruction is based on the Sphagnum δ 13 C cellulose /temperature dependency observed in calibration stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…DR5; Loader et al, 2016). Many studies on carbon isotope composition of mosses concluded that moisture availability exerts a critical influence (Rice and Giles, 1996;Price et al, 1997;Ménot and Burns, 2001;Loisel et al, 2009), although other studies indicated potential influence of temperature, probably due to intrinsic relation between temperature and moisture-related environmental factors (e.g., Ménot and Burns, 2001;Moschen et al, 2011). Other influencing factors include CO 2 concentration (White et al, 1994) and recycled CH 4derived CO 2 (Price et al, 1997 (Ménot-Combes et al, 2002;Zanazzi and Mora, 2005).…”
Section: Evaluation Of Evaporative Effect On Oxygen Isotopes Of Moss mentioning
confidence: 99%
“…DR5; Loader et al, 2016). Many studies on carbon isotope composition of mosses concluded that moisture availability exerts a critical influence (Rice and Giles, 1996;Price et al, 1997;Ménot and Burns, 2001;Loisel et al, 2009), although other studies indicated potential influence of temperature, probably due to intrinsic relation between temperature and moisture-related environmental factors (e.g., Ménot and Burns, 2001;Moschen et al, 2011). Other influencing factors include CO 2 concentration (White et al, 1994) and recycled CH 4derived CO 2 (Price et al, 1997 (Ménot-Combes et al, 2002;Zanazzi and Mora, 2005).…”
Section: Evaluation Of Evaporative Effect On Oxygen Isotopes Of Moss mentioning
confidence: 99%